Risk factors and incidence of unplanned re-operation after transumbilical single-hole laparoscopic appendectomy in children - Luo, Yuanyuan; Zhang, Hong; Wu, Qiang; Li, Qianlong; Ye, Zhihua; Zeng, Jixiao; Xu, Xiaogang (Frontiers in Pediatrics, 2025)
PurposeThis study aims to investigate the factors associated with unplanned re-operations (UR) following transumbilical single-hole laparoscopic appendectomy (TUSILA) in pediatric patients.MethodsWe conducted a retrospective analysis of clinical data from children diagnosed with acute appendicitis (AA) who underwent TUSILA at our center between January 2020 and January 2024. All the operations were performed under single-port laparoscopy, including two methods of appendectomy, intra-TUSILA and extra-TUSILA. Patients were categorized into the UR and control groups to compare baseline characteristics, clinical data, postoperative management, and surgical outcomes.ResultsThe study included 188 patients (110 males and 78 females), with 4 (2.1%) in the UR group. Within the UR group, three cases (75%) necessitated re-operation due to adhesive intestinal obstruction, while one case (25%) was due to an appendiceal remnant fistula. The baseline characteristics, operation duration, intraoperative blood loss, surgeon experience, and postoperative fasting times showed no significant difference between the two groups (all P > 0.05). However, the incidences of procedures beyond standard TUSILA, lateral peritoneum lysis, appendiceal perforation, complicated appendicitis as confirmed by pathology, drainage tube placement, and the length of antibiotic duration were significantly higher in the UR group compared to the control group (all P < 0.05).ConclusionA notable percentage of pediatric patients undergoing TUSILA experience UR, primarily due to adhesive ileus, with a substantial proportion potentially linked to surgical technical errors and postoperative management.